Persepsi Karyawan Terhadap Kompensasi, Motivasi, dan Kepemimpinan Transformasional Sebagai Faktor Pembentuk Kepuasan Kerja - Ramadhani, Adilah Putri; Masarroh, Azzah; Hasanah, Raudatul; Surman, Surman (Indo-MathEdu Intellectuals Journal, 2025)
Job satisfaction is an important element in human resource management, influenced by various organizational aspects. This study aims to thoroughly examine how compensation, motivation, and transformational leadership affect employees' perceptions and job satisfaction through a comprehensive literature review. The approach used is descriptive qualitative with a literature study method. Data were obtained from secondary sources such as books and scientific journal articles published between 2020 and 2025. Data analysis was conducted through thematic analysis (Braun & Clarke, 2006) by synthesizing theories from various related literature. The analysis findings indicate that employees' views on compensation are not limited to financial aspects but also include fairness and recognition. Work motivation arises from both intrinsic and extrinsic factors that influence each other in building job satisfaction. Transformational leadership, with its four dimensions, has been shown to play an important role in shaping employee job satisfaction. These three elements interact dynamically to achieve maximum job satisfaction. This study emphasizes the need for a holistic strategy that combines compensation, motivation, and transformational leadership to continuously enhance employee job satisfaction.